Defining the Current Position of the Gastronomy Field in Turkey. Issue 1 (2nd January 2021) - Seyitoğlu, Faruk
ABSTRACT: The present study aims to investigate and define the current position of the gastronomy field in Turkey. In order to achieve this, interviews were held with academics who are involved in the field of gastronomy. According to the analysis of the data, the nature of gastronomy both as a field and a concept is 'multi-defined/comprehensive', has a 'multi-component' structure, is 'interdisciplinary', 'lacks a specific (unique) research question', and 'is accepted mainly as practical area'. It then became clear that there have been some developments, such as 'gaining attention and developing as an educational field', 'the increase in the number of publications and opportunities to publish' and 'the formation of a scientific community'. Some deficiencies and necessities have also emerged that are related to issues as 'theoretical background', 'education', 'research area', 'the number of publications and opportunities to publish', 'methods' and 'the ideal gastronomy academic profile'.